Decision Support Tools for River Restoration: The Implementation of the “River Habitat Survey” Methodology on the River Selho (Guimarães Municipality, Northwest Portugal) - Francisco Costa; António Vieira (Hydrology, 2021)
The river habitat survey (RHS) system is a method used to assess the physical features and quality of rivers, which was developed to assist in the conservation and recovery of riverside habitats. The RHS takes into account the need to characterize areas of intervention from a hydromorphological point of view, in order to introduce corrective measures aimed at restoring degraded sections and habitats, and increasing local biodiversity. In this paper, we present the results obtained from the application of the RHS methodology to the River Selho, in the municipality of Guimarães (Portugal). The transects that we defined were strongly influenced by anthropic actions that have modified the riverside habitats, the artificialization of the river channel, and the urban occupation of the banks. Taking into account the results, we can point out the main problems that currently affect the hydromorphological quality of the transects analyzed in the River Selho, as well as identify the originating factors: the excessive silting of the watercourse; morphometric changes, with an emphasis on the narrowing and modification of the channel and the banks; as well as the massive destruction of the riparian zone. This study shows that the application of the RHS methodology is a useful tool for the management of degraded riverside areas.